Smart Farming On IoT-Based Aeroponik Systems - Simanungkalit, Erwinsyah; Husna, Mardhiatul; Tarigan , Jenni Sari; Suriyadi, Suriyadi (Politeknik Ganesha Medan, 2023)
The high population growth has an impact on all sectors, one of which has an impact on the agricultural sector as a result of the transfer of agricultural land. This diversion also has an impact on food supplies and ecosystem damage. To deal with these problems, it is necessary to seek the use of technology as a solution in the digitalization era. This research combines aeroponic plants with the help of Internet of Things (IoT) technology.This method has been used by many people to grow plants, especially short-lived vegetable crops such as lettuce, kale, spinach and other types. In planting using this method indoors it really requires special attention compared to planting outdoors. For example, the level of nutrient density, lighting, temperature and humidity in the room. But there are still some farmers or people who don't understand farming with an aeroponic system and how many benefits are felt. By using a smart system, the monitoring and supervision system for plants will get better, so thatfarmer or someone can get the result the more and the better the results by utilizing a piece of land that is not used or on the balcony of the house without having to bother renting other people's land. In order for the expected harvest to be abundant or even more, there are several conditions. Results obtained in this study is by monitoring aeroponic plants produce high quality vegetable crops compared to conventional systems that is.